Proses Pelaksanaan Manajemen Risiko Pada Pembiayaan Murabahah Di BPRS Haji Miskin Pandai Sikek Kabupaten Tanah Datar, Provinsi Sumatera Barat - Darwin Darwin; Saparuddin Siregar (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
Islamic banks function as an intermediary institution that is collecting funds from the public and channeling funds to the people who need it in the form of financing. In the business world, both in the fields of industry, trade, transportation and other business fields will not be separated from the need for funds. Every bank must have risks faced, including the provision of financing to customers who need to increase business capital. Most of the Poor Hajj BPRS customers who apply for murabaha financing are traders. The income earned from these businesses sometimes increases and decreases, resulting in frequent bottlenecks when payment of debt to Islamic banking parties. Then the company needs to supervise and manage the risk of financing that will be provided to customers with the aim of reducing the occurrence of bad loans.